Analysis of the negative charges injected into a SiO2/SiNx stack using plasma charging technology for field‐effect passivation on a boron‐doped silicon surface. (4th October 2020) - Min, Kwan Hong; Hwang, Jeong‐Mo; Cho, Eunwan; Song, Hee‐eun; Park, Sungeun; Rohatgi, Ajeet; Kim, Donghwan; Lee, Hae‐Seok; Kang, Yoonmook; Ok, Young‐Woo; Kang, Min Gu
Abstract: We investigated field‐effect passivation by injecting negative charges into SiO2 /SiNx stack using a plasma charge injection technique. The Si/SiO2 /SiNx samples exhibited a very high flat‐band shift with a high injected negative charge density (>3.0 × 10 13 cm 2 ) after plasma negative charge injection; this density was higher than that for the well‐known Al2 O3 layer. Most injected negative charges were present within approximately 90 nm of the surface of the SiNx layer deposited by plasma‐enhanced chemical vapor deposition (PECVD) when comparing the capacitance–voltage analysis results obtained while etching the SiNx film considering four assumptions of the injected negative charge distribution. The saturation current density in a 90‐ohm/sq boron emitter decreased from 90 to 50 fA/cm 2 after negative charge injection, which is equivalent to the J 0e of the structure passivated with an Al2 O3 /SiNx stack. Six‐inch n ‐type bifacial cells with an approximately 100‐ohm/sq boron emitter passivated with SiO2 /SiNx displayed an approximately 0.2% increase in absolute cell efficiency after negative charge injection. In addition, n ‐PERT bifacial cells with a high boron sheet resistance of 150 ohm/sq exhibited a 1.0% or higher absolute efficiency enhancement from a relatively low precharging efficiency of approximately 19.0%. We also demonstrated that the final efficiency after charging was comparable with n ‐PERT bifacial cells with Al2 O3 passivation, suggesting that the proposed process is a potential low‐cost alternative method that could replace expensive Al2 O3 processes. Abstract : We investigated field‐effect passivation by injecting negative charges into SiO2 /SiNx stack using a plasma charging technique. It was confirmed that the negative charge injected into the SiO2 /SiNx stack was distributed at 90 nm of the SiNx surface. The saturation current density in a 90‐ohm/sq boron emitter decreased from 90 to 50 fA/cm 2 after charge injection. n ‐type PERT bifacial cells with an approximately 100‐ohm/sq boron emitter passivated with SiO2 /SiNx displayed an 0.2% increase in absolute cell efficiency after charge injection.